Antibacterial and antiviral treatment method for metal member

By forming a complex roughened shape on the surface of the metal component, the problem of insufficient antiviral and antibacterial properties in the existing technology is solved, and higher antiviral activity and antibacterial effects are achieved.

CN120769932APending Publication Date: 2025-10-10MEC CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202480014581.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-15
Filing Date
2024-02-08
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

The antiviral and antibacterial properties of metal components in the existing technology are insufficient, especially the antiviral activity value after sandblasting is not ideal and needs to be further improved.

Method used

The roughening process is performed by contacting the surface of the metal component with a micro-etching agent to form a complex roughened shape, and the treatment is performed using an organic acid, inorganic acid, alkali or hydrogen peroxide micro-etching agent, preferably a combination of pre-treatment, formal treatment and post-treatment steps.

Benefits of technology

The antibacterial and antiviral properties of metal components are significantly improved. The complex roughened shape formed is more effective than sandblasting, and can significantly reduce the infection titer of viruses and bacteria and increase the antiviral activity value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120769932A_ABST
    Figure CN120769932A_ABST
Patent Text Reader

Abstract

This antibacterial and antiviral treatment method for a metal member is provided with a roughening treatment step for bringing a microetchant into contact with the surface of the metal member to form a roughened shape on the surface of the metal member, thereby imparting antibacterial and antiviral properties to the surface of the metal member. The roughening treatment step preferably comprises three steps, namely a pretreatment step, a formal treatment step, and a post-treatment step. The microetchant is preferably at least one microetchant selected from the group consisting of an organic acid-based microetchant, an inorganic acid-based microetchant, an alkali-based microetchant, and a hydrogen peroxide-based microetchant. The metal member is preferably aluminum, an aluminum alloy, copper, or a copper alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an antibacterial and antiviral treatment method for a metal component. Background Art

[0002] In recent years, in particular, in order to prevent infection with COVID-19, the so-called novel coronavirus infection, there has been a demand for antibacterial or antiviral properties to be imparted to the surfaces of components and the like that are touched by human hands.

[0003] The following patent document 1 describes an antiviral surface treatment method, which randomly forms countless fine bumps "with a specific bump spacing width and a depth width of the concave portion" by performing a blasting treatment (hereinafter also referred to as "sand blasting") on the surface of a component by spraying a material, thereby giving the surface of the component an antiviral effect.

[0004] Background Art Literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 2022-28394 Summary of the Invention

[0007] [Problems to be Solved by the Invention]

[0008] One criterion for evaluating antiviral properties is the "antiviral activity value." In the technique described in Patent Document 1, while the comparative object (stainless steel plate) showed no antiviral activity, after undergoing an antiviral surface treatment, the antiviral activity value was shown to be 0.4 to 0.7 after 24 hours at 25°C. However, the present inventors conducted research and determined that, because sandblasting involves blasting the surface of a component with a material, it only creates a convex shape toward the back of the component. Therefore, the antibacterial and antiviral properties achieved by the technique described in Patent Document 1 are insufficient, and further improvements in antibacterial and antiviral properties are needed.

[0009] In view of the above circumstances, an object of the present invention is to provide an antibacterial and antiviral treatment method for a metal member, which can impart excellent antibacterial and antiviral properties to the metal member.

[0010] [Technical means to solve the problem]

[0011] The above-mentioned problems can be solved by the following structure. The present invention relates to an antibacterial and antiviral treatment method (1) for a metal component, characterized in that it comprises a roughening treatment step, wherein the roughening treatment step is to form a roughened shape on the surface of the metal component by bringing a micro-etching agent into contact with the surface of the metal component, thereby imparting antibacterial and antiviral properties to the surface of the metal component.

[0012] The antibacterial and antiviral treatment method (2) for metal components is preferably as follows, wherein in the antibacterial and antiviral treatment method (1) for metal components, the roughening treatment process has three steps: a pretreatment step, a main treatment step, and a post-treatment step.

[0013] Preferably, the antibacterial and antiviral treatment method (3) for metal components is as follows, wherein in the antibacterial and antiviral treatment method (1) or (2) for metal components, the microetching agent is at least one microetching agent selected from the group consisting of organic acid microetching agents, inorganic acid microetching agents, alkaline microetching agents and hydrogen peroxide microetching agents.

[0014] The following antibacterial and antiviral treatment method (4) for metal components is preferred, wherein in any one of the antibacterial and antiviral treatment methods (1) to (3) for metal components, the metal component is aluminum, aluminum alloy, copper or copper alloy.

[0015] [Effects of the Invention]

[0016] The antibacterial and antiviral treatment method for metal components according to the present invention can provide a metal component that exhibits not only antibacterial properties but also excellent antiviral properties, specifically, high antiviral activity values. While the reason for achieving superior antibacterial and antiviral properties compared to sandblasting is not entirely clear, the following factors are hypothesized.

[0017] Since the surface of the component is subjected to a blasting treatment in which a jet of ejected material is sprayed, sandblasting can basically only form a shape that is convex toward the back of the component. On the other hand, in the antibacterial and antiviral treatment method for a metal component of the present invention, the surface of the metal component is roughened by bringing a microetching agent into contact with the surface of the metal component during the roughening treatment process, thereby forming a roughened shape on the surface of the metal component. Therefore, as shown in the following experimental results, a shape that is much more complex than the roughened surface formed by sandblasting can be formed. In addition, the inventors have discovered for the first time that the antiviral and antibacterial properties that can be obtained by the complex shape (roughened shape) formed on the surface of the metal component by the roughening treatment process of the present invention are significantly better than the antiviral and antibacterial properties that can be brought to the metal surface by other treatment methods, especially sandblasting. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] [ Figure 1 ] is a scanning electron microscope photograph (magnification 1500 times) of the surface of the (untreated) metal component of Comparative Example 1.

[0019] [ Figure 2 ] is a scanning electron microscope photograph (magnification 5000 times) of the surface of the (untreated) metal component of Comparative Example 1.

[0020] [ Figure 3 ] is a scanning electron microscope photograph (magnification 1500 times) of the surface of the metal component produced in Example 1.

[0021] [ Figure 4 ] is a scanning electron microscope photograph (magnification 5000 times) of the surface of the metal component produced in Example 1.

[0022] [ Figure 5 ] is a scanning electron microscope photograph (magnification 1500 times) of the surface of the metal component produced in Example 2.

[0023] [ Figure 6 ] is a scanning electron microscope photograph (5000x magnification) of the surface of the metal component produced in Example 2.

[0024] [ Figure 7 ] is a scanning electron microscope photograph (magnification 1500 times) of the surface of the (untreated) metal component of Comparative Example 2.

[0025] [ Figure 8 ] is a scanning electron microscope photograph (5000x magnification) of the surface of the (untreated) metal component of Comparative Example 2.

[0026] [ Figure 9 ] is a scanning electron microscope photograph (magnification 1500 times) of the surface of the metal component produced in Example 3.

[0027] [ Figure 10 ] is a scanning electron microscope photograph (magnification 5000 times) of the surface of the metal component produced in Example 3.

[0028] [ Figure 11 ] is a scanning electron microscope photograph (magnification 1500 times) of the surface of the metal component produced in Example 4.

[0029] [ Figure 12 ] is a scanning electron microscope photograph (5000x magnification) of the surface of the metal component produced in Example 4.

[0030] [ Figure 13 ] is a scanning electron microscope photograph (magnification 1500 times) of the surface of an untreated stainless steel member that has not been roughened.

[0031] [ Figure 14 ] is a scanning electron microscope photograph (5000x magnification) of the surface of an untreated stainless steel member that has not been subjected to roughening treatment.

[0032] [ Figure 15] is a scanning electron microscope photograph (magnification 1500 times) of the surface of an untreated stainless steel component after sandblasting.

[0033] [ Figure 16 ] is a scanning electron microscope photograph (5000x magnification) of the surface of an untreated stainless steel component after sandblasting. DETAILED DESCRIPTION

[0034] The antibacterial and antiviral treatment method for metal components of the present invention includes a roughening treatment process, wherein a micro-etching agent is brought into contact with the surface of the metal component to form a roughened shape on the surface of the metal component, thereby imparting antibacterial and antiviral properties to the surface of the metal component.

[0035] As the metal components that can be used in the present invention, there can be mentioned: aluminum, aluminum alloy, copper, copper alloy, nickel, nickel alloy, stainless steel, titanium, titanium alloy, iron or iron alloy, etc. Among these, aluminum, aluminum alloy, copper or copper alloy is preferably used as the metal component in the present invention. The shape or size of the metal component can be appropriately designed according to the use purpose after bringing antibacterial and antiviral properties. In addition, in the sandblasting process, since the material is sprayed on the surface of the component, the processing surface (surface) of the metal component to bring antibacterial and antiviral properties is preferably a flat surface, but in the antibacterial and antiviral treatment method for the metal component of the present invention, since the surface of the metal component is roughened by making the micro-etching agent contact the surface of the metal component, the processing surface of the metal component is not limited to a flat surface, and antibacterial and antiviral properties can be brought to the surface of any shape, which is also a feature.

[0036] As the micro-etching agent used in the roughening treatment step, for example, an organic acid-based micro-etching agent, an inorganic acid-based micro-etching agent, an alkali-based micro-etching agent, or a hydrogen peroxide-based micro-etching agent can be used.

[0037] Examples of the organic acid-based micro-etching agent include micro-etching agents composed of an aqueous solution containing an organic acid, a metal ion source, a halide ion source, and the like.

[0038] Examples of the inorganic acid-based micro-etching agent include micro-etching agents composed of an acidic aqueous solution containing an inorganic acid, a metal ion source, a halide ion source, and the like.

[0039] Examples of the alkaline microetching agent include a microetching agent composed of an aqueous solution containing an alkali source, an amphoteric metal ion source, nitrate ions, a sulfur-containing compound, and the like.

[0040] Examples of the hydrogen peroxide-based micro-etching agent include a micro-etching agent composed of an aqueous solution containing hydrogen peroxide and sulfuric acid as main components.

[0041] In the antibacterial and antiviral treatment method for metal components of the present invention, the roughening treatment process can be performed in a single step. However, to further improve the antibacterial and antiviral properties of the manufactured metal component, the roughening treatment process is preferably performed in two steps. It is particularly preferred to perform the roughening treatment process in three steps: a pretreatment step, a main treatment step, and a post-treatment step. An embodiment of performing the roughening treatment process in three steps is described below.

[0042] In the pretreatment step, for example, the following step can be exemplified: immersing at least the treated surface of the metal component in dilute nitric acid, a hydrogen peroxide-based soft etchant composed of an aqueous solution containing hydrogen peroxide and sulfuric acid as main components, or an alkaline soft etchant such as an aqueous solution containing an alkali source, an amphoteric metal ion source, nitrate ions, a sulfur-containing compound, etc. The treatment temperature can be, for example, 15 to 40°C, and the treatment time can be, for example, approximately 3 seconds to 10 minutes.

[0043] In the main treatment step, for example, the following step can be exemplified, namely, immersing at least the treatment surface of the metal member in the organic acid-based microetchant, inorganic acid-based microetchant, alkaline microetchant, or hydrogen peroxide-based microetchant, etc. The treatment temperature can be, for example, 10 to 40° C., and the treatment time can be, for example, about 5 seconds to 10 minutes.

[0044] The post-treatment step may include, for example, immersing at least the treated surface of the metal member in dilute nitric acid, etc. The treatment temperature may be, for example, 15 to 40° C., and the treatment time may be, for example, approximately 3 to 40 seconds.

[0045] After the roughening process, a complex roughened pattern is formed on the surface of the metal component. This imparts excellent antibacterial and antiviral properties to the metal component's surface. The following describes specific examples of the complex roughened pattern formed on the surface of a metal component after the roughening process.

[0046] The antibacterial and antiviral treatment method for metal components of the present invention can be used to manufacture metal components with excellent antibacterial and antiviral properties. The antiviral activity value that shows the degree of antiviral property can be calculated with reference to JIS R1756:2020 (visible light responsive photocatalyst, antiviral, film adhesion method) and according to the following calculation formula.

[0047] V D =Log(B D )-Log(C D ) (1)

[0048] In the formula (1), V Drepresents the antiviral activity value, D represents the dark area, B represents the infection titer of the unprocessed product, and C represents the infection titer of the processed product.

[0049] As described above, the antibacterial and antiviral treatment method for metal components of the present invention can be used to manufacture metal components with excellent antibacterial and antiviral properties. Therefore, the antibacterial and antiviral treatment method for metal components of the present invention is particularly suitable as a treatment method for imparting antibacterial and antiviral properties to metal components used for the following purposes: household appliances, residential building materials / equipment, toilet-related facilities / supplies, kitchen-related facilities / supplies, bathroom-related facilities / supplies, office equipment and office supplies, printing (printed materials, laminated products or paper), transportation machinery, industrial machinery and industrial supplies (packaging materials / films for films, food, etc., packaging materials, etc.), medical care, nursing care, health care, communication-related accessories, pet supplies, daily necessities (shoes, cleaning products, cosmetics, etc.), etc.

[0050] Example

[0051] An example of an embodiment of the present invention will be described below, but the present invention is not limited to this description.

[0052] Ref.(-) (glass plate) was prepared as an "unprocessed product". Next, an unused aluminum alloy plate (A-6063-t5) (40 mm × 40 mm × t2 mm) was prepared as an unprocessed aluminum alloy member that was not subjected to roughening treatment. A scanning electron microscope photograph (magnification 1500 times) of the surface of this (unprocessed) aluminum alloy member is shown in FIG. Figure 1 The scanning electron microscope photograph (5000 times magnification) is shown in Figure 2 . refer to Figure 1 and Figure 2 Photos, especially reference Figure 2 From the photograph of , it can be seen that the surface of the (untreated) aluminum alloy member has no irregularities at all and is nearly mirror-like. The (untreated) aluminum alloy member is referred to as Comparative Example 1.

[0053] Example 1

[0054] A roughening treatment process (three steps, namely, a pre-treatment step, a main treatment step, and a post-treatment step) was performed on an unused aluminum alloy plate (A-6063-t5) (40 mm × 40 mm × t2 mm) under the following conditions (hereinafter, the roughening treatment process in Example 1 is referred to as "roughening treatment 1"). The conditions for each step are as follows.

[0055] (Preprocessing step)

[0056] The surface of the aluminum alloy plate to be treated was immersed in dilute nitric acid (allowed to stand). Treatment temperature: 35° C. Treatment time: 5 to 10 minutes.

[0057] (Formal processing steps)

[0058] Following the pretreatment, the surface of the aluminum alloy plate to be treated was immersed in an alkaline microetchant (an aqueous solution containing an alkali source, an amphoteric metal ion source, nitrate ions, a sulfur-containing compound, etc.) (allowed to stand). The treatment temperature was 35°C and the treatment time was 4 minutes.

[0059] (Post-processing step)

[0060] Following the main treatment, the surface of the aluminum alloy plate to be treated was immersed in dilute nitric acid (allowed to stand). Treatment temperature: room temperature. Treatment time: 30 seconds.

[0061] Following post-treatment, ultrasonic cleaning was performed in pure water for 1 minute.

[0062] A scanning electron microscope photograph (magnification 1500 times) of the surface of the aluminum alloy member obtained after the roughening treatment step (roughening treatment 1) of Example 1 (referred to as "(roughening treatment 1) aluminum alloy member") is shown in FIG. Figure 3 The scanning electron microscope photograph (5000 times magnification) is shown in Figure 4 .according to Figure 3 From the photo of , it can be seen that a complex roughening shape is formed on the entire surface of the aluminum alloy component through the roughening treatment step 1. Figure 4 From the photograph, it can be seen that a convex shape in random directions is formed on the surface of the aluminum alloy component.

[0063] For reference, a scanning electron microscope photograph (magnification 1500 times) of the surface of an untreated stainless steel member that has not been subjected to roughening treatment is shown in FIG. Figure 13 The scanning electron microscope photograph (5000 times magnification) is shown in Figure 14 The scanning electron microscope photograph (magnification 1500 times) of the surface of the untreated stainless steel component after sandblasting is shown in Figure 15 The scanning electron microscope photograph (5000 times magnification) is shown in Figure 16 .right Figure 13 and Figure 15 ,and Figure 14 and Figure 16 By comparison, it is clear that since sandblasting can only form a convex shape toward the back of the component, it is impossible to form a complex roughened shape on the stainless steel surface. Figure 3 and Figure 4 Photos, especially reference Figure 4From the photographs, it can be seen that a much more complex roughening shape is formed on the surface of the aluminum alloy component (roughening treatment 1) than on the "stainless steel surface subjected to sandblasting".

[0064] Example 2

[0065] An unused aluminum alloy plate (A-6063-t5) (40 mm × 40 mm × t2 mm) was subjected to a roughening treatment process (three steps: pretreatment step, main treatment step, and post-treatment step) under the following conditions (hereinafter, the roughening treatment process in Example 2 is referred to as "roughening treatment 2"). The conditions for each step are as follows.

[0066] (Preprocessing step)

[0067] The surface of the aluminum alloy plate to be treated was immersed in an alkaline soft etchant (allowed to stand) at a temperature of 35° C. and for 1 minute.

[0068] (Formal processing steps)

[0069] Following the pretreatment, the surface of the aluminum alloy plate to be treated was immersed in an inorganic acid microetchant (an aqueous solution containing an inorganic acid, an amphoteric metal ion source, a halide ion source, etc.) (allowed to stand). Treatment temperature: 30°C. Treatment time: 10 minutes.

[0070] (Post-processing step)

[0071] Following the main treatment, the surface of the aluminum alloy plate to be treated was immersed in dilute nitric acid (allowed to stand). Treatment temperature: room temperature. Treatment time: 30 seconds.

[0072] Following post-treatment, ultrasonic cleaning was performed in pure water for 1 minute.

[0073] A scanning electron microscope photograph (magnification 1500 times) of the surface of the aluminum alloy member obtained after the roughening treatment step (roughening treatment 2) of Example 2 (referred to as "(roughening treatment 2) aluminum alloy member") is shown in FIG. Figure 5 The scanning electron microscope photograph (5000 times magnification) is shown in Figure 6 .according to Figure 5 From the photo of , it can be seen that a complex roughening shape is formed on the entire surface of the aluminum alloy component through the roughening treatment step 2. Figure 6 From the photograph, it can be seen that the surface of the aluminum alloy component has a convex shape in any direction. In other words, it can be seen that the surface of the aluminum alloy component has a much more complex roughened shape than the "sandblasting treatment that only produces a convex shape toward the back of the component."

[0074] [Antiviral evaluation]

[0075] Ref.(-) (glass plate) was evaluated as an unprocessed product, and the antiviral properties of the (untreated) aluminum alloy member of Comparative Example 1, and the “aluminum alloy member on which the antiviral treatment method for a metal member was performed ((roughening treatment 1) aluminum alloy member and (roughening treatment 2) aluminum alloy member)” of Examples 1-2 were evaluated and compared using the following conditions.

[0076] [Test specifications]

[0077] Reference: JIS R1756:2020 (Visible light responsive photocatalyst, antiviral, film tightness method)

[0078] [Unprocessed product name]

[0079] Ref.(-) (glass plate)

[0080] [Test product name]

[0081] (untreated) aluminum alloy member (Comparative Example 1), (roughening treatment 1) aluminum alloy member (Example 1), (roughening treatment 2) aluminum alloy member (Example 2)

[0082] [Test product (aluminum alloy member) size]

[0083] 40 mm x 40 mm x t2 mm

[0084] [n number]

[0085] n = 1

[0086] [Test phages]

[0087] • Phage Qβ (NBRC 20012) [host Escherichia coli (NBRC 106373)], the results of which are shown in Table 1.

[0088] • Phage φ6 (NBRC 105899, non-JIS specification) [host Pseudomonas syringae (NBRC 14084)], the results of which are shown in Table 2.

[0089] [Dilution of test phages]

[0090] 1 / 500 NB

[0091] [Stérilisation of test products]

[0092] Sterilization was performed under UV (Ultraviolet) 254 nm for 15 minutes each for the front and back surfaces

[0093] [Conditions for action]

[0094] Temperature 25℃, dark place, action time 0 hours, 4 hours

[0095] [Adhesive film]

[0096] Polypropylene film (VF-10, KOKUYO), 30mm x 30mm

[0097] [Table 1]

[0098]

[0099] Test phage: bacteriophage Qβ (instead of norovirus)

[0100] Inoculation phage concentration: 6.0×10 6 pfu / mL

[0101] Inoculation volume: 0.225 mL / sample

[0102] *1“E+06” means “×10 6 ”

[0103] *2 Reference value calculated using the following formula with reference to JIS standards

[0104] V D :Antiviral activity value:[V D =Log(B D )-Log(C D )]

[0105] D: Dark area, B: Infectivity of unprocessed product, C: Infectivity of processed product

[0106] As shown in Table 1, the infectivity titers of the aluminum alloy components (roughening treatment 1) and (roughening treatment 2) obtained in Examples 1 and 2 significantly decreased after 4 hours in the dark at 25°C. Furthermore, along with the significant decrease in infectivity titer, the antiviral activity value also increased to 5 after 4 hours in the dark at 25°C. These results indicate that the "metal components produced using the antiviral treatment method for metal components" in Examples 1 and 2 exhibit significant antiviral effects due to the highly complex roughening patterns formed on the metal components' surfaces.

[0107] [Table 2]

[0108]

[0109] Experimental phage: φ6 phage (instead of influenza virus, COVID-19)

[0110] Inoculation phage concentration: 1.2×10 7 pfu / mL

[0111] Inoculation volume: 0.225 mL / sample

[0112] *1“E+06” means “×10 6 ”

[0113] *2 Reference value calculated using the following formula with reference to JIS standards

[0114] V D :Antiviral activity value:[V D =Log(B D )-Log(C D )]

[0115] D: Dark area, B: Infectivity of unprocessed product, C: Infectivity of processed product

[0116] As described in Table 2, the infection titers of the aluminum alloy components (roughening treatment 1) and (roughening treatment 2) obtained in Example 1 and Example 2 were significantly reduced after 4 hours in the dark at 25°C. In addition, along with the significant reduction in infection titer, the antiviral activity value also increased to 5.3 after 4 hours in the dark at 25°C. Based on these results, it can be understood that the "metal components obtained by the antiviral treatment method for metal components" in Example 1 and Example 2 have a very complex roughened shape formed on the surface of the metal components. Therefore, regardless of the test phage, that is, whether it is norovirus, influenza virus, or coronavirus, it has a significant effect in terms of antiviral properties.

[0117] [Antibacterial evaluation]

[0118] Using Ref.(-) (glass plate) as an unprocessed product, the antibacterial properties of the (untreated) aluminum alloy component of Comparative Example 1 and the "aluminum alloy components to which the antibacterial treatment method for metal components has been implemented ((roughening treatment 1) aluminum alloy components and (roughening treatment 2) aluminum alloy components)" of Examples 1 to 2 were evaluated under the following conditions.

[0119] [Test specifications]

[0120] Reference JIS Z2801:2012

[0121] [Unprocessed product name]

[0122] Ref.(-)(Glass Plate)

[0123] [Test product name]

[0124] (Untreated) aluminum alloy member (Comparative Example 1), (Roughening Treatment 1) aluminum alloy member (Example 1), (Roughening Treatment 2) aluminum alloy member (Example 2)

[0125] [Test product (aluminum alloy member) size]

[0126] 40mm×40mm×t2 mm

[0127] [n quantity]

[0128] n=1

[0129] [Test bacteria]

[0130] Staphylococcus aureus (NBRC 12732). The results are shown in Table 3.

[0131] Escherichia coli (NBRC 3972). The results are shown in Table 4.

[0132] [Dilution of test phage]

[0133] 1 / 500NB

[0134] [Sterilization of test samples]

[0135] Sterilize at UV 254nm (15 minutes each for the surface and back)

[0136] [Action conditions]

[0137] Temperature 25℃, dark place, action time 0 hours, 8 hours

[0138] [Adhesive film]

[0139] Polypropylene film (VF-10, KOKUYO), 30mm×30mm

[0140] [Table 3]

[0141]

[0142] Test bacteria: Staphylococcus aureus

[0143] Inoculum concentration: 8.4×10 5 cfu / mL

[0144] Inoculation volume: 0.225 mL / sample

[0145] *1“E+03” means “×10 3 ”

[0146] *2 Reference value calculated using the following formula with reference to JIS standards

[0147] R: Antibacterial activity value: R = U t -A t

[0148] U t: Logarithmic value of the number of viable bacteria per unit area after the reaction of the unprocessed test piece (Ref.(-)), A t : Logarithmic value of the number of viable bacteria per unit area of ​​the antibacterial treated test piece after reaction

[0149] As shown in Table 3, the number of viable bacteria in the aluminum alloy components (roughening treatment 1) and (roughening treatment 2) obtained in Examples 1 and 2 was significantly reduced after 8 hours in a dark place at 25°C. In addition, along with the significant reduction in the number of viable bacteria, the antibacterial activity value also increased to 3.8 to 4.2 after 8 hours in a dark place at 25°C. Based on these results, it can be understood that the "metal components obtained by the antibacterial treatment method for metal components" in Examples 1 and 2 have a significant effect on antibacterial properties due to the very complex roughening shape formed on the surface of the metal components.

[0150] [Table 4]

[0151]

[0152] Test bacteria: Escherichia coli

[0153] Inoculum concentration: 3.5×10 5 cfu / mL

[0154] Inoculation volume: 0.225 mL / sample

[0155] *1“E+03” means “×10 3 ”

[0156] *2 Reference value calculated using the following formula with reference to JIS standards

[0157] R: Antibacterial activity value: R = U t -A t

[0158] U t : Logarithmic value of the number of viable bacteria per unit area after the reaction of the unprocessed test piece (Ref.(-)), A t : Logarithmic value of the number of viable bacteria per unit area of ​​the antibacterial treated test piece after reaction

[0159] As described in Table 4, the number of live bacteria in the (roughening treatment 1) aluminum alloy components and (roughening treatment 2) aluminum alloy components obtained in Example 1 and Example 2 was significantly reduced after 8 hours in the dark at 25°C. In addition, as the number of live bacteria decreased significantly, the antibacterial activity value also increased to 4.5 after 8 hours in the dark at 25°C. Based on these results, it can be understood that the "metal components obtained by the antibacterial treatment method for metal components" in Example 1 and Example 2 have a very complex roughened shape formed on the surface of the metal components. Therefore, regardless of the test phage, that is, whether it is Staphylococcus aureus or Escherichia coli, it has a significant effect in terms of antibacterial properties.

[0160] Ref.(-) (glass plate) was prepared as an "unprocessed product". Next, an unused copper member (50 mm × 50 mm × t1.3 mm) was prepared as an unprocessed copper member that was not subjected to roughening treatment. A scanning electron microscope photograph (magnification 1500 times) of the surface of this (unprocessed) copper member is shown in FIG. Figure 7 The scanning electron microscope photograph (5000 times magnification) is shown in Figure 8 . refer to Figure 7 and Figure 8 Photos, especially reference Figure 8 , it can be seen from the photograph that there is no unevenness at all on the surface of the (untreated) copper member, and it is almost a mirror surface. The (untreated) copper member is referred to as Comparative Example 2.

[0161] Example 3

[0162] A roughening process (three steps: pre-treatment, main treatment, and post-treatment) was performed on an unused copper plate (50 mm × 50 mm × t1.3 mm) under the following conditions (hereinafter, the roughening process in Example 3 is referred to as "roughening process 3"). The conditions for each step are as follows.

[0163] (Preprocessing step)

[0164] The surface of the copper plate to be treated was sprayed with dilute hydrochloric acid. Treatment temperature: room temperature. Treatment time: 10 seconds.

[0165] (Formal processing steps)

[0166] Following the pretreatment, the surface of the copper plate to be treated was sprayed with an organic acid microetchant (an aqueous solution containing an organic acid, a metal ion source, a halide ion source, etc.) at a treatment temperature of 30° C. for 60 seconds.

[0167] (Post-processing step)

[0168] Following the main treatment, the surface of the copper plate to be treated was sprayed with dilute hydrochloric acid. Treatment temperature: room temperature. Treatment time: 15 seconds.

[0169] A scanning electron microscope photograph (magnification 1500 times) of the surface of the copper member obtained after the roughening treatment step (roughening treatment 3) of Example 3 (referred to as "(roughening treatment 3) copper member") is shown in FIG. Figure 9 The scanning electron microscope photograph (5000 times magnification) is shown in Figure 10 .according to Figure 9 From the photo of , it can be seen that a complex roughening shape is formed on the entire surface of the copper component through the roughening treatment step 3. Figure 10 In the photograph, it can be seen that a shape convex in any direction is formed on the surface of the copper component. In other words, it can be seen that a much more complicated roughening shape is formed on the surface of the copper component than the sandblasting treatment that can only form a shape convex only toward the back side of the component.

[0170] Example 4

[0171] A roughening process (three steps: pre-treatment, main treatment, and post-treatment) was performed on an unused copper plate (50 mm × 50 mm × t1.3 mm) under the following conditions (hereinafter, the roughening process in Example 4 is referred to as "roughening process 4"). The conditions for each step are as follows.

[0172] (Preprocessing step)

[0173] The surface of the copper plate to be treated was sprayed with dilute hydrochloric acid. Treatment temperature: room temperature. Treatment time: 10 seconds.

[0174] (Formal processing steps)

[0175] Following the pretreatment, the surface of the copper plate to be treated was sprayed with an organic acid microetchant (an aqueous solution containing an organic acid, a metal ion source, a halide ion source, etc.) at a treatment temperature of 30° C. for 150 seconds.

[0176] (Post-processing step)

[0177] Following the main treatment, the surface of the copper plate to be treated was sprayed with dilute hydrochloric acid. Treatment temperature: room temperature. Treatment time: 15 seconds.

[0178] A scanning electron microscope photograph (magnification 1500 times) of the surface of the copper member obtained after the roughening treatment step (roughening treatment 4) of Example 4 (referred to as "(roughening treatment 4) copper member") is shown in FIG. Figure 11 The scanning electron microscope photograph (5000 times magnification) is shown in Figure 12.according to Figure 11 From the photograph of , it can be seen that a complex roughening shape is formed on the entire surface of the copper component through the roughening treatment step 4. Figure 12 In the photograph, it can be seen that a shape convex in any direction is formed on the surface of the copper component. In other words, it can be seen that a much more complicated roughening shape is formed on the surface of the copper component than the sandblasting treatment that can only form a shape convex only toward the back side of the component.

[0179] [Antiviral evaluation]

[0180] Using Ref.(-) (glass plate) as an unprocessed product, the antiviral properties of the (untreated) copper component of Comparative Example 2 and the "copper components to which the antiviral treatment method for metal components has been implemented ((roughening treatment 3) copper components and (roughening treatment 4) copper components)" of Examples 3 to 4 were evaluated using the following conditions.

[0181] [Test specifications]

[0182] Reference JIS R1756:2020 (visible light responsive photocatalyst, antiviral, membrane adhesion method)

[0183] [Unprocessed product name]

[0184] Ref.(-)(Glass Plate)

[0185] [Test product name]

[0186] (Untreated) copper member (Comparative Example 2), (Roughening Treatment 3) copper member (Example 3), (Roughening Treatment 4) copper member (Example 4)

[0187] [Test product (copper component) size]

[0188] 50mm×50mm×t1.3 mm

[0189] [n quantity]

[0190] n=1

[0191] [Test phage]

[0192] Bacteriophage Qβ (NBRC 20012) [host Escherichia coli (NBRC 106373)], the results are shown in Table 5.

[0193] The results are shown in Table 6 for bacteriophage φ6 (NBRC 105899, non-JIS standard) [host: Pseudomonas syringae (NBRC 14084)].

[0194] [Dilution of test phage]

[0195] 1 / 20 NB

[0196] [sterilization of test article]

[0197] Bactericidal test at UV 254 nm (15 minutes for each of front and back surfaces)

[0198] [conditions for action]

[0199] Temperature: 25°C, dark place, action time: 0 minutes, 30 minutes

[0200] [adhesion film]

[0201] Polypropylene film (VF-10, KOKUYO), 40 mm x 40 mm

[0202] [Table 5]

[0203]

[0204] Test bacteriophage: bacteriophage Qβ (instead of norovirus)

[0205] Inoculum concentration: 5.7 x 10 6 pfu / mL

[0206] Inoculum amount: 0.4 mL / sample

[0207] *1 "E+06" indicates "x 10 6 "

[0208] *2 Reference value calculated according to the following formula, based on JIS standards

[0209] V D : antiviral activity value: [V D = Log(B D ) - Log(C D )]

[0210] D: dark place, B: infection titer of unprocessed product, C: infection titer of processed product

[0211] As described in Table 5, the copper member obtained in Example 3 and the copper member obtained in Example 4 (roughening treatment 3) and (roughening treatment 4) showed a significant decrease in the infection titer after 30 minutes in a dark place at 25°C. In addition, with the significant decrease in the infection titer, the antiviral activity value also increased to 5.3 after 30 minutes in a dark place at 25°C. From these results, it can be understood that the "metal member produced by the antiviral treatment method using a metal member" of Example 3 and Example 4 exerted a significant effect in terms of antiviral properties because a very complex roughened shape was formed on the surface of the metal member.

[0212] [Table 6]

[0213]

[0214] Experimental phage: φ6 phage (instead of influenza virus, COVID-19)

[0215] Inoculation phage concentration: 1.3×10 7 pfu / mL

[0216] Inoculation volume: 0.4 mL / sample

[0217] *1“E+06” means “×10 6 ”

[0218] *2 Reference value calculated using the following formula with reference to JIS standards

[0219] V D :Antiviral activity value:[V D =Log(B D )-Log(C D )]

[0220] D: Dark area, B: Infectivity of unprocessed product, C: Infectivity of processed product

[0221] As described in Table 6, the infection titer of the copper components (roughening treatment 3) and (roughening treatment 4) obtained in Example 3 and Example 4 decreased significantly after 30 minutes in the dark at 25°C. In addition, along with the significant decrease in infection titer, the antiviral activity value also increased to 5.6 after 30 minutes in the dark at 25°C. Based on these results, it can be understood that the "metal components obtained by the antiviral treatment method of metal components" in Example 3 and Example 4 have a very complex roughened shape formed on the surface of the metal components. Therefore, regardless of the test phage, that is, whether it is norovirus, influenza virus, or coronavirus, it has a significant effect in terms of antiviral properties.

[0222] [Antibacterial evaluation]

[0223] Using Ref.(-) (glass plate) as an unprocessed product, the antibacterial properties of the (untreated) copper component of Comparative Example 2 and the "copper components subjected to the antibacterial treatment method for metal components ((roughening treatment 3) copper components and (roughening treatment 4) copper components)" of Examples 3 to 4 were evaluated under the following conditions.

[0224] [Test specifications]

[0225] Reference JIS Z2801:2012

[0226] [Unprocessed product name]

[0227] Ref.(-)(Glass Plate)

[0228] [Test product name]

[0229] (Untreated) copper member (Comparative Example 2), (Roughening Treatment 3) copper member (Example 3), (Roughening Treatment 4) copper member (Example 4)

[0230] [Test product (copper component) size]

[0231] 50mm×50mm×t1.3 mm

[0232] [n quantity]

[0233] n=1

[0234] [Test bacteria]

[0235] Staphylococcus aureus (NBRC 12732). The results are shown in Table 7.

[0236] Escherichia coli (NBRC 3972). The results are shown in Table 8.

[0237] [Dilution of test phage]

[0238] 1 / 20NB (Staphylococcus aureus), 1 / 500NB (Escherichia coli)

[0239] [Sterilization of test samples]

[0240] Sterilize at UV 254nm (15 minutes each for the surface and back)

[0241] [Action conditions]

[0242] Temperature 25℃, dark place, action time 0 minutes, 15 minutes

[0243] [Adhesive film]

[0244] Polypropylene film (VF-10, KOKUYO), 40mm×40mm

[0245] [Table 7]

[0246]

[0247] Test bacteria: Staphylococcus aureus

[0248] Inoculum concentration: 6.5×10 5 cfu / mL

[0249] Inoculation volume: 0.4 mL / sample

[0250] *1“E+03” means “×10 3 ”

[0251] *2 Reference value calculated using the following formula with reference to JIS standards

[0252] R: Antibacterial activity value: R = U t -A t

[0253] U t : Logarithmic value of the number of viable bacteria per unit area after the reaction of the unprocessed test piece (Ref.(-)), A t : Logarithmic value of the number of viable bacteria per unit area of ​​the antibacterial treated test piece after reaction

[0254] As shown in Table 7, the number of viable bacteria in the copper components (roughening treatment 3) and (roughening treatment 4) obtained in Examples 3 and 4 was significantly reduced after 15 minutes in a dark place at 25°C. In addition, as the number of viable bacteria decreased significantly, the antibacterial activity value also increased to 3.5 to 3.7 after 15 minutes in a dark place at 25°C. Based on these results, it can be understood that the "metal components obtained by the antibacterial treatment method for metal components" in Examples 3 and 4 have a significant effect on antibacterial properties because a very complex roughening shape is formed on the surface of the metal components.

[0255] [Table 8]

[0256]

[0257] Test bacteria: Escherichia coli

[0258] Inoculum concentration: 6.7×10 5 cfu / mL

[0259] Inoculation volume: 0.4 mL / sample

[0260] *1“E+03” means “×10 3 ”

[0261] *2 Reference value calculated using the following formula with reference to JIS standards

[0262] R: Antibacterial activity value: R = U t -A t

[0263] U t : Logarithmic value of the number of viable bacteria per unit area after the reaction of the unprocessed test piece (Ref.(-)), A t : Logarithmic value of the number of viable bacteria per unit area of ​​the antibacterial treated test piece after reaction

[0264] As described in Table 8, the number of live bacteria in the copper components (roughening treatment 3) and (roughening treatment 4) obtained in Examples 3 and 4 was significantly reduced after 15 minutes in a dark place at 25°C. In addition, as the number of live bacteria decreased significantly, the antibacterial activity value also rose to 3.9 after 15 minutes in a dark place at 25°C. Based on these results, it can be understood that the "metal components obtained by the antibacterial treatment method for metal components" in Examples 3 and 4 have a very complex roughened shape formed on the surface of the metal components. Therefore, regardless of the test bacteria, that is, whether it is Staphylococcus aureus or Escherichia coli, it has a significant effect in terms of antibacterial properties.

Claims

1. A method for antibacterial and antiviral treatment of metal components, characterized in that A roughening treatment step is provided in which a micro-etching agent is brought into contact with the surface of the metal component to form a roughened shape on the surface of the metal component, thereby imparting antibacterial and antiviral properties to the surface of the metal component.

2. The antibacterial and antiviral treatment method for metal components according to claim 1, wherein: The roughening process includes three steps: a pre-processing step, a main processing step, and a post-processing step.

3. The antibacterial and antiviral treatment method for metal components according to claim 1, wherein: The micro-etching agent is at least one micro-etching agent selected from the group consisting of an organic acid-based micro-etching agent, an inorganic acid-based micro-etching agent, an alkali-based micro-etching agent, and a hydrogen peroxide-based micro-etching agent.

4. The antibacterial and antiviral treatment method for metal components according to claim 1, wherein: The metal component is aluminum, aluminum alloy, copper or copper alloy.

Citation Information

Patent Citations

  • Antivirus surface treatment method of member and antivirus member

    JP2022028394A

  • Copper etchant and method of etching

    CN101098989A

  • Microetching agent for copper, copper surface roughening method and wiring board production method

    CN111094628A

  • Anti-microbial copper or brass surfaces

    GB2468704A

  • Phosphor bronze alloy whose antibacterial property is amplified by roughening surface using anodic oxidation method in which the surface is subjected to immersion treatment for a fixed time

    JP2021123786A